ASSESSING THE EFFECT OF SCHOOL CULTURE ON INSTRUCTIONAL LEADERSHIP IN MALDIVES - Mohamed, Ahmed; Moosa, Visal; Yusoff, Sazali (Universitas Pendidikan Indonesia, 2020)
Organisational culture and leadership are linked to each other across various organisations including schools. This research attempts to examine the influence of school culture on instructional leadership of principals in schools of Maldives. A total of 145 teachers participated in the study. The data were statistically analysed using descriptive and inferential statistics. The result showed that all the dimensions of school culture are significantly associated with all the three dimensions of instructional leadership. The findings also revealed that three dimensions of school culture - ‘professional development’, ‘unity of purpose’ and ‘teacher collaboration’ - have a significant impact on instructional leadership. Based on the statistical results, implications of the findings were discussed in the context of school culture, and leadership. Consequently, suggestions for future research were also explored.